Stainless steel foam filtering material and preparation method thereof
Through the combination of stainless steel powder and foam sponge frame materials, the stainless steel foam filter material solves the shortcomings of existing stainless steel filter mesh and ceramic filter materials in terms of filtration accuracy, durability and price, achieving efficient filtration, durability and economy.
Patent Information
- Application Number
- CN202411876579.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
AI Technical Summary
The existing stainless steel filter mesh and ceramic filter materials have shortcomings in filtration accuracy, durability and price, resulting in unsatisfactory filtration effect, easy to block and high prices.
Using a preparation method of combining stainless steel powder and foam sponge frame material, a slurry is formed by heating the adhesive and stainless steel powder, soaking and extruding, drying and sintering to form a stainless steel foam filter material with high porosity and high porosity.
It realizes high-efficiency filtration of stainless steel foam filter materials, acid and alkali corrosion resistance, high temperature resistance, wear resistance, easy cleaning and high filtration efficiency, significantly improving the filtration effect and product quality.
Smart Images

Figure CN119633495A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter material application, in particular to a stainless steel foam filter material and a preparation method thereof. Background Art
[0002] The selection of filter materials in slurry production is crucial and directly affects the quality of the product. At present, filter materials are classified from the application structure form, including filter cloth, filter paper, hose, filter screen, polyester filter cloth, PVDF filter membrane, fluoroplastic filter, fiberglass slurry filter, etc.; from the material itself, it includes quartz sand filter material, ceramic filter material, polyester fiber filter material, stainless steel mesh filter material, activated carbon filter material, etc. Among them, ceramic filter material has a fine filtering effect, and can be resistant to high temperature, corrosion and wear. At present, domestic ceramic filter materials generally use microporous ceramic membrane filtration. The advantage of this filter material is high filtration efficiency; stainless steel mesh filter material is mainly woven from 304 and 316 stainless steel materials. The stainless steel mesh filter material has high strength, can increase the service life of the ultrafiltration membrane, has a wide range of applications, and is often used to filter liquids and gases.
[0003] Stainless steel filter mesh is suitable for filtering melts such as chemical fiber spinning, short fiber, ultrafine fiber, leather, non-woven fabrics, plastic granulation, sheet extrusion, masterbatch, rubber, etc. Stainless steel filter mesh is divided into multi-layer spot welding filter mesh and multi-layer edged filter mesh according to the process, which can be rectangular, round, ring, rectangular, waist-shaped, and special-shaped. Although the stainless steel filter mesh has the characteristics of acid resistance, alkali resistance, high temperature resistance, strong tension and friction, due to the process structure characteristics of its multi-layer mesh welding, the filtering accuracy is limited, resulting in some fine particles or impurities cannot be effectively intercepted during the filtering process, affecting the filtering effect; due to the small aperture of the stainless steel filter mesh, and the easy accumulation of impurities and particles during use, it is easy to be blocked, which not only affects the filtering efficiency, but also may cause damage or pollution to the filtered material; stainless steel filter mesh is prone to rust when used in harsh environments for a long time or improperly maintained, which not only affects the appearance and service life of the filter mesh, but also may reduce its filtering effect; compared with other filter materials, the price of stainless steel filter mesh is higher.
[0004] Ceramic filter materials have the advantages of high temperature resistance, corrosion resistance, and high-efficiency filtration, but they also have some obvious disadvantages, such as high brittleness, poor ductility and toughness, and are easily damaged when subjected to large heat load fluctuations or mechanical stress; poor thermal shock resistance. Due to its poor thermal conductivity and high brittleness, ceramic filter materials are difficult to withstand rapid temperature changes, which may limit their use in some application scenarios with large temperature changes; although the pore size of ceramic filter materials can be specified, impurities and particulate matter are easily accumulated during long-term use, leading to blockage, which not only affects the filtration efficiency, but also may increase the difficulty of cleaning and maintenance; the production process is complex and the raw material cost is high, resulting in the price of ceramic filter materials being generally high. Summary of the invention
[0005] In order to solve the above-mentioned technical problems, the present invention provides a stainless steel foam filter material and a preparation method thereof. The preparation method is simple and easy to operate. The prepared stainless steel foam filter material product is resistant to acid and alkali corrosion, wear and high temperature, light in weight, high in strength, strong in fluid permeability, easy to clean and high in filtration efficiency.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing a stainless steel foam filter material, characterized by being achieved through the following steps: 1) Prepare raw materials: weigh a certain weight of stainless steel powder according to production needs, prepare adhesive, and cut into several foam sponge skeleton materials of required size; 2) Roughening the foam sponge skeleton material: roughening a number of cut foam sponge skeleton materials with a roughening liquid to make the surface roughness of the foam sponge skeleton material reach 2 μm, and drying for standby use; 3) Prepare stainless steel slurry: Use a heating device to heat the prepared adhesive liquid stored in the container, set the temperature to 50-70°C, wait for the adhesive liquid to completely dissolve, pour the stainless steel powder into the adhesive liquid, stir evenly to form a stainless steel powder slurry; 4) Preparing a stainless steel foam block green body: placing the foam sponge skeleton material processed in step 2) in the middle of the stainless steel slurry for soaking and slurrying, and after completion, taking out the foam sponge skeleton material and squeezing out the excess slurry in the foam sponge skeleton material by mechanical equipment to prepare a stainless steel foam block green body; 5) Drying the green body: Place the green body of the stainless steel foam block prepared in step 4) on a stainless steel flat bracket for drying, turn it over and dry it every 4-8 hours until the dryness reaches more than 90% for use; 6) Debinding and sintering: The dried green body prepared in step 5) is placed in a sintering furnace for sintering. The green body begins to be debinded after the temperature reaches 60-80°C. After that, the temperature of the sintering furnace is controlled to gradually increase for debinding, and finally sintered at the highest sintering temperature of 1200-1300°C. The overall operation time is set to 1.5-3 hours to form a finished stainless steel foam filter material. After cooling, the product can be inspected; 7) Product inspection: For finished stainless steel foam filter materials, the porosity is 20-30 per inch, the porosity is ≥82%, the filtration accuracy is 2.5-3.5mm, and the filtration efficiency is ≥99.6%; 8) Packaging and warehousing: Stainless steel foam filter material products that pass the inspection are trimmed and packaged according to the required size.
[0007] The stainless steel powder in step 1) is 316L stainless steel powder, 304 stainless steel powder or a powder formed by a combination of the two in proportion, and the particle size is ≤-500#.
[0008] The foam sponge skeleton material in step 1) is 15-25ppi polyurethane foam sponge.
[0009] The adhesive in step 1) is made of polyvinyl alcohol, bone glue and purified water, wherein the weight ratio of polyvinyl alcohol to bone glue is set to 1.5-2.
[0010] In step 2), the foam sponge skeleton material is roughened by using a strong oxidizing acid solution as the roughening liquid, so that the surface of the foam sponge skeleton material is microscopically rough to facilitate slurry attachment.
[0011] In step 4), a double-roll extrusion device is used to squeeze the foam sponge skeleton material after the slurry is coated.
[0012] In step 5), the green body is dried by natural airing, drying with a hair dryer or drying equipment.
[0013] In step 6), a support plate for placing the green body is arranged in the sintering furnace. The support plate is made of a material having a shrinkage coefficient equivalent to that of the green body. The green body is placed on the support plate for sintering to prevent deformation.
[0014] A stainless steel foam filter material is formed by evenly distributing stainless steel powder adhesive slurry on a foam sponge skeleton material carrier and sintering it into a fixed shape. A number of fine pores are evenly distributed inside, with a porosity of 20-30 per inch, a permeability of ≥82%, a filtration accuracy of 2.5-3.5mm, and a filtration efficiency of more than 99.6%. It is used for filtering, cooling, and evenly mixing multiple slurries in production.
[0015] The present invention combines the characteristics of current filter materials with different structures, functions and properties, designs a stainless steel foam filter material product and a preparation method thereof, makes special improvements on the basis of the traditional ceramic filter material processing technology, and obtains a stainless steel foam filter product with better filtering effect, high strength, light weight, high temperature resistance up to 800°C, corrosion resistance and wear resistance. The stainless steel foam filter product can be applied to slurry filtration and temperature reduction in the slurry production industry. In particular, after multiple varieties of slurry flow out through the present invention, not only can common impurities in the slurry be filtered out, but also gel impurities can be filtered out through the high porosity, high-strength cutting and strong fluid patency of the stainless steel foam filter material. At the same time, the mixing of multiple slurries is made more uniform and delicate, the fineness of the production process of slurry products is improved, and the production quality of the final product is improved.
[0016] Specifically, in the preparation method of the present invention, the surface of the foam sponge skeleton material is made microscopically rough by coarsening the foam sponge skeleton material, thereby solving the problem of heavy specific gravity of stainless steel powder and difficulty in slurry hanging; in the degreasing stage, a step-by-step heating method is adopted to solve the problem of crack defects in the green body caused by excessive temperature rise in the furnace; in the sintering stage, a support plate made of a material equivalent to the shrinkage rate of the green body is provided under the green body as a support, thereby solving the problem of low density of the green body and easy deformation caused by its own gravity, and at the same time, the degreasing sintering time and temperature are strictly controlled to ensure the product quality of the sintered stainless steel foam filter material; through product inspection, the porosity of the stainless steel foam filter material of the present invention reaches 20-30 / inch, the porosity is ≥82%, the porosity is evenly distributed, and the filtration accuracy is as high as 2.5-3.5mm after testing, and the filtration efficiency is higher than 99.6%, and the filtration effect is significantly higher than the filtration material currently used in similar production industries, and its size can be cut at will, the weight is light, and it is easy to transport and store, and it can be flexibly applied to various required filtration processes and related equipment, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the microstructure of the stainless steel foam filter material of the present invention. DETAILED DESCRIPTION
[0018] The method for preparing the stainless steel foam filter material of the present invention is achieved by the following steps: 1) Prepare raw materials: weigh a certain weight of stainless steel powder according to production needs, prepare adhesive, and cut into several foam sponge skeleton materials of required size; 2) Roughening the foam sponge skeleton material: roughening a number of cut foam sponge skeleton materials with a roughening liquid to make the surface roughness of the foam sponge skeleton material reach 2 μm, and drying for standby use; 3) Prepare stainless steel slurry: Use a heating device to heat the prepared adhesive liquid stored in the container, set the temperature to 50-70°C, wait for the adhesive liquid to completely dissolve, pour the stainless steel powder into the adhesive liquid, stir evenly to form a stainless steel powder slurry; 4) Preparing a stainless steel foam block green body: placing the foam sponge skeleton material processed in step 2) in the middle of the stainless steel slurry for soaking and slurrying, and after completion, taking out the foam sponge skeleton material and squeezing out the excess slurry in the foam sponge skeleton material by mechanical equipment to prepare a stainless steel foam block green body; 5) Drying the green body: Place the green body of the stainless steel foam block prepared in step 4) on a stainless steel flat bracket for drying, turn it over and dry it every 4-8 hours until the dryness reaches more than 90% for use; 6) Debinding and sintering: The dried green body prepared in step 5) is placed in a sintering furnace for sintering. The green body begins to be debinded after the temperature reaches 60-80°C. After that, the temperature of the sintering furnace is controlled to gradually increase for debinding, and finally sintered at the highest sintering temperature of 1200-1300°C. The overall operation time is set to 1.5-3 hours to form a finished stainless steel foam filter material. After cooling, the product can be inspected; 7) Product inspection: For finished stainless steel foam filter materials, the porosity is 20-30 per inch, the porosity is ≥82%, the filtration accuracy is 2.5-3.5mm, and the filtration efficiency is ≥99.6%; 8) Packaging and warehousing: Stainless steel foam filter material products that pass the inspection are trimmed and packaged according to the required size.
[0019] As a preferred embodiment, in the present invention, the stainless steel powder in step 1) is 316L stainless steel powder, 304 stainless steel powder or a powder formed by a combination of the two in proportion, and the particle size is ≤-500#.
[0020] As a preferred embodiment, in the present invention, the foam sponge skeleton material in step 1) is a 15-25ppi polyurethane foam sponge.
[0021] As a preferred embodiment, in the present invention, the adhesive in step 1) is made of polyvinyl alcohol, bone glue and purified water, wherein the weight ratio of polyvinyl alcohol to bone glue is set to 1.5-2.
[0022] As a preferred embodiment, in the present invention, in step 2), the foam sponge skeleton material is roughened, and the roughening liquid is a strong oxidizing acidic solution, so that the surface of the foam sponge skeleton material is microscopically rough to facilitate slurry attachment.
[0023] As a preferred embodiment, in the present invention, in step 4), a double-roll extrusion device is used to squeeze the foam sponge skeleton material after the slurry is coated.
[0024] As a preferred embodiment, in the present invention, the green body is dried in step 5) by natural airing, drying with a hair dryer or drying equipment.
[0025] As a preferred embodiment, in the present invention, in step 6), a support plate for placing the green body is arranged in the sintering furnace, the support plate is made of a material having a shrinkage rate equivalent to that of the green body, and the green body is placed on the support plate for sintering to prevent deformation.
[0026] like Figure 1 As shown, a stainless steel foam filter material prepared according to the preparation method is formed by evenly distributing stainless steel powder adhesive slurry on a foam sponge skeleton material carrier and sintering to shape it. A number of fine pores are evenly distributed inside, the porosity is 20-30 per inch, the porosity is ≥82%, the filtration accuracy is 2.5-3.5mm, and the filtration efficiency is 99.6%. It is used for filtering, cooling, and evenly mixing multiple slurries in production.
[0027] The preparation method of the present invention is described in detail below through specific examples.
[0028] 1) Prepare raw materials: select 500 grams of 316L stainless steel powder for standby use, with a particle size of ≤-500#. The specific chemical composition of 304 stainless steel powder and 316L stainless steel powder belongs to the common knowledge of technicians in this field, and will not be introduced in detail here; the adhesive is prepared by mixing 5 grams of polyvinyl alcohol, 3 grams of bone glue, and 200 milliliters of pure water in a stainless steel barrel and soaking for 1 hour; select polyurethane foam sponge as the foam skeleton carrier, and cut the foam sponge into a rectangular block with a size of 100*100*50mm each, weighing 9.4 grams; 2) Roughening the foam sponge skeleton material: The cut foam sponge skeleton material is roughened by a roughening liquid, so that the roughness of the surface of the foam sponge skeleton material reaches 2μm, and then dried for use; the roughening liquid generally contains chromic anhydride and sulfuric acid, which is a strong oxidizing acidic solution, which can remove the residual dirt on the surface of the foam sponge skeleton and has a strong descaling ability. After roughening, the surface of the foam sponge skeleton is microscopically rough, fine and uniform, which is convenient for the subsequent slurry hanging operation; 3) Preparation of stainless steel slurry: Use an electric ceramic stove to heat the prepared adhesive liquid stored in a stainless steel barrel, set the temperature to 50-70°C, and when the adhesive liquid is completely dissolved without particles, pour the stainless steel powder into the adhesive liquid, stir evenly to form a stainless steel powder slurry; the specific heating temperature also depends on the dissolution of the adhesive liquid, and can be set to 50°C, 60°C, 70°C and adjusted at any time according to the situation; 4) Preparing a stainless steel foam block green body: placing the foam sponge skeleton material processed in step 2) in the middle of the stainless steel slurry for soaking and slurrying, taking it out with flat-nosed pliers after completion, and squeezing out the excess slurry in the foam sponge skeleton material by using a double-roll extrusion device to prepare a stainless steel foam block green body; specifically, placing the foam sponge skeleton with slurry on the platform, starting the roller wheels, adjusting the gap between the roller wheels, and pushing the foam sponge skeleton covered with slurry into the double rollers, and squeezing out the excess slurry by rotating the double rollers; 5) Drying the green body: Place the green body of the stainless steel foam block prepared in step 4) on a stainless steel flat bracket for drying, turn it over for drying every 4-8 hours, and keep it ready for use when the dryness reaches more than 90%; when the sunshine is good, it can be dried naturally with a slightly longer drying time, such as 8 hours, or it can be dried with a hair dryer or drying equipment with a shorter drying time, such as a drying machine can achieve single-side drying in 4 hours, while a hair dryer may take 6 hours, depending on the specific situation; 6) Sintering and debinding: Place the dried green body prepared in step 5) in a sintering furnace for sintering. Debinding begins at 60-80°C. After the debinding process begins, the temperature of the sintering furnace is controlled to rise gradually for debinding. Finally, the temperature is raised to the highest sintering temperature of 1200-1300°C. The overall operation time is set to 1.5-3 hours to form a finished stainless steel foam filter material. After cooling, the product can be inspected. The purpose of debinding is to remove organic matter added to the powder to ensure the smooth progress of the subsequent sintering process. Therefore, the selection of debinding temperature needs to comprehensively consider multiple factors to ensure the debinding effect and product quality. In actual operation, multiple tests and optimizations should be carried out according to the specific situation to determine the optimal debinding temperature. In the process of step-by-step heating, as the number of tests increases, the appropriate frequency, temperature rise span and the optimal debinding temperature range can be found, so that the green body can achieve the best debinding effect and lay a good foundation for the sintering process; after the debinding is completed, the temperature is still rising, and the final sintering temperature is controlled at 1200-1300℃, which is also determined according to the production process at the time. For example, 1200℃, 1250℃, and 1300℃ are selected. The overall operation time will also be adjusted according to the temperature adjustment. When the temperature is 1200℃, the operation time can be controlled at 3 hours, when the temperature is 1250℃, the overall operation time can be controlled at 2 hours, and when the temperature is 1300℃, the overall operation time can be shorter, controlled at 1.5 hours, and the corresponding adjustments can be made according to the specific process; 7) Product inspection: For finished stainless steel foam filter materials, the porosity is 20-30 per inch, the porosity is ≥82%, the filtration accuracy is 2.5-3.5mm, and the filtration efficiency is ≥99.6%; 8) Packaging and warehousing: Stainless steel foam filter material products that pass the inspection are trimmed and packaged according to the required size.
[0029] In step 6), since the density of the foam sponge skeleton slurry green body is small, there is gravity during liquid phase sintering, and the sintered finished product is prone to deformation. Therefore, for larger products, a material with a shrinkage rate equivalent to it can be selected as a support plate to support the green body to prevent deformation and ensure product quality.
[0030] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing a stainless steel foam filter material, characterized in that: This is accomplished by the following steps: 1) Prepare raw materials: weigh a certain weight of stainless steel powder according to production needs, prepare adhesive, and cut into several foam sponge skeleton materials of required size; 2) Roughening the foam sponge skeleton material: roughening a number of cut foam sponge skeleton materials with a roughening liquid to make the surface roughness of the foam sponge skeleton material reach 2 μm, and drying for standby use; 3) Prepare stainless steel slurry: Use a heating device to heat the prepared adhesive liquid stored in the container, set the temperature to 50-70°C, wait for the adhesive liquid to completely dissolve, pour the stainless steel powder into the adhesive liquid, stir evenly to form a stainless steel powder slurry; 4) Preparing a stainless steel foam block green body: placing the foam sponge skeleton material processed in step 2) in the middle of the stainless steel slurry for soaking and slurrying, and after completion, taking out the foam sponge skeleton material and squeezing out the excess slurry in the foam sponge skeleton material by mechanical equipment to prepare a stainless steel foam block green body; 5) Drying the green body: Place the green body of the stainless steel foam block prepared in step 4) on a stainless steel flat bracket for drying, turn it over and dry it every 4-8 hours until the dryness reaches more than 90% for use; 6) Debinding and sintering: The dried green body prepared in step 5) is placed in a sintering furnace for sintering. The green body begins to be debinded after the temperature reaches 60-80°C. After that, the temperature of the sintering furnace is controlled to gradually increase for debinding, and finally sintered at the highest sintering temperature of 1200-1300°C. The overall operation time is set to 1.5-3 hours to form a finished stainless steel foam filter material. After cooling, the product can be inspected; 7) Product inspection: For finished stainless steel foam filter materials, the porosity is 20-30 per inch, the porosity is ≥82%, the filtration accuracy is 2.5-3.5mm, and the filtration efficiency is ≥99.6%; 8) Packaging and warehousing: Stainless steel foam filter material products that pass the inspection are trimmed and packaged according to the required size.
2. The method for preparing a stainless steel foam filter material according to claim 1, characterized in that: The stainless steel powder in step 1) is 316L stainless steel powder, 304 stainless steel powder or a powder formed by a combination of the two in proportion, and the particle size is ≤-500#.
3. The method for preparing a stainless steel foam filter material according to claim 1, characterized in that: The foam sponge skeleton material in step 1) is 15-25ppi polyurethane foam sponge.
4. The method for preparing a stainless steel foam filter material according to claim 1, characterized in that: The adhesive in step 1) is made of polyvinyl alcohol, bone glue and purified water, wherein the weight ratio of polyvinyl alcohol to bone glue is set to 1.5-2.
5. The method for preparing a stainless steel foam filter material according to claim 1, characterized in that: In step 2), the foam sponge skeleton material is roughened by using a strong oxidizing acid solution as the roughening liquid, so that the surface of the foam sponge skeleton material is microscopically rough to facilitate slurry attachment.
6. The method for preparing a stainless steel foam filter material according to claim 1, characterized in that: In step 4), a double-roll extrusion device is used to squeeze the foam sponge skeleton material after the slurry is coated.
7. The method for preparing a stainless steel foam filter material according to claim 1, characterized in that: In step 5), the green body is dried by natural airing, drying with a hair dryer or drying equipment.
8. The method for preparing a stainless steel foam filter material according to claim 1, characterized in that: In step 6), a support plate for placing the green body is arranged in the sintering furnace. The support plate is made of a material having a shrinkage coefficient equivalent to that of the green body. The green body is placed on the support plate for sintering to prevent deformation.
9. A stainless steel foam filter material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: It is made of stainless steel powder adhesive slurry evenly distributed on a foam sponge skeleton material carrier and sintered to shape. It has a number of evenly distributed pores inside, a porosity of 20-30 per inch, a permeability of ≥82%, a filtration accuracy of 2.5-3.5mm, and a filtration efficiency of more than 99.6%. It is used for filtering, cooling, and evenly mixing multiple slurries in production.